The early news catches the attention: On the relative price impact of similar economic indicators - Dieter Hess; Alexandra Niessen (University of Cologne, Centre for Financial Research (CFR), 2007)
There is strong evidence that macroeconomic releases influence prices in financial markets. However, why do markets react to some announcements while they ignore others with a similar content? Based on a Bayesian learning model, we show that market impact is mainly determined by information quality and timeliness of a release. To test the model's implications, we analyze the successive introduction of the two largest German business surveys: the well-known IFO index and the recently introduced ZEW economic indicator. In line with the model's prediction, we find a diminishing market impact of the IFO index after the ZEW indicator was introduced.
Keywords: E44; G14; 330; Bayesian Learning; Macroeconomic Announcements; Information Processing